Medicine in the context of culture - Ye. I. Kirilenko (Бюллетень сибирской медицины)
The idea of the need for a dialogue of medicine and Humanities insisted declares itself in national and world scientific thought. In modern literature is a brilliant example of combining medical and humanitarian offers an American researcher Lynn Peyer (1945–2001). The "Medicine and Сulture: Varieties of Treatment in the United States, England, West Germany, and France" (1988) she explores the problem of cultural meanings as a factor in forming the medical experience. In the article on the basis of results from l. Peyer, dealt with a situation based on health consciousness and practice of appropriate cultural context, the characteristics of Western medical and cultural tradition is complemented by analysis of domestic realities.